NOTCH and Graft-Versus-Host Disease - Di Ianni, Mauro; Del Papa, Beatrice; Baldoni, Stefano; Di Tommaso, Ambra; Fabi, Bianca; Rosati, Emanuela; Natale, Annalisa; Santarone, Stella; Olioso, Paola; Papalinetti, Gabriele; Giancola, Raffaella; Accorsi, Patrizia; et al. (Frontiers in Immunology, 2018)
In allogeneic hematopoietic stem cell transplantation, which is the major curative therapy for hematological malignancies, T cells play a key role in the development of graft-versus-host disease (GvHD). NOTCH pathway is a conserved signal transduction system that regulates T cell development and differentiation. The present review analyses the role of the NOTCH signaling as a new regulator of acute GvHD. NOTCH signaling could also represent a new therapeutic target for GvHD.